Mortimer and the sword Excalibur - "Aiken, Joan" (Frances Lincoln Children's Books: London, 2015)
Arabel Jones and her beloved but impossible raven, Mortimer, are sent out to play in the local park. An enormous hole is being dug in the park and rumour has it that King Arthur's Round Table is buried there. None of this interests Mortimer, however; his fancy has been taken by the giant grass-cutting machine, the LawnSabre
Keywords: Humorous fiction